The evolutionary origin of SARS-CoV-2 - Gao, Feng (Henry Stewart Talks, 2020)
SARS-CoV-2: a product of zoonosis, SARS-CoV-2 may have been mutating towards its current form for decades, Evolutionary recombination events leading to SARS-CoV-2: bats & pangolins, Genetic similarity and differences with other lethal coronaviruses: SARS-1 & MERS, Phenotypic comparison of SARS-CoV-2 with other coronaviruses, Genetic evidence debunking claims that SARS-CoV-2 is a deliberate human-engineered virus, Probability, location and species of possible future emergence of zoonotic viruses, Implications for SARS-CoV-2 vaccine development